Saliva Quantification of SARS-CoV-2 in Real-Time PCR From Asymptomatic or Mild COVID-19 Adults - Carrouel, Florence; Gadea, Emilie; Esparcieux, Aurélie; Dimet, Jérome; Langlois, Marie Elodie; Perrier, Hervé; Dussart, Claude; Bourgeois, Denis (Frontiers in Microbiology, 2022)
The fast spread of Covid-19 is related to the highly infectious nature of SARS-CoV-2. The disease is suggested to be transmitted through saliva droplets and nasal discharge. The saliva quantification of SARS-CoV-2 in real-time PCR from asymptomatic or mild COVID-19 adults has not been fully documented. This study analyzed the relationship between salivary viral load on demographics and clinical characteristics including symptoms, co-morbidities in 160 adults diagnosed as COVID-19 positive patients recruited between September and December 2020 in four French centers. Median initial viral load was 4.12 log10 copies/mL (IQR 2.95 - 5.16; range 0 – 10.19 log10 copies/mL). 68.6% of adults had no viral load detected. A median load reduction of 23% was observed between 0-2 days and 3-5 days, and of 11% between 3-5 days and 6-9 days for the delay from onset of symptoms to saliva sampling. No significant median difference between no-symptoms vs. symptoms patients was observed. Charge was consistently similar for the majority of the clinical symptoms excepted for headache with a median load value of 3.78 log10 copies/mL [1.95 - 4.58] (P<0.003). SARS-CoV-2 RNA viral load was associated with headache and gastro-intestinal symptoms. The study found no statistically significant difference in viral loads between age groups, sex, or presence de co-morbidity. The study reinforces the hypothesis that the oral cavity is actively involved in the transmission of SARS-CoV-2.